Emotional Turbulance in Adolescents - Bhatia, Ranjana (JOURNAL OF INDIAN EDUCATION, 2012)
t is said that mind should not be allowed to master us. Instead, we should be able to master our mind. Mind apparently is the root cause of creating all problems whether mental, emotional or physical. In adolescents, havoc is created as mind keeps mastering their body and creating problems resulting into emotional turmoil. The mind of adolescents is flooded with questions they are unable to find answer for. These unanswered questions manifest in the form of search for identity, low self esteem, worries and anxieties related to physical changes, and uncontrolled emotional stage. These troubling emotions can lead to frustration, unrestrained anger, mental instability and various other problems that may cause harm to the adolescents. This is an age when they need help that can come by understanding their tribulations. By identifying visible warning signs of turbulence, help can be rendered to them by various measures that may assist adolescents to pass through this difficult phase with ease. Effective listening skills, building their confidence, healthy relationship and open discussion may help them to sail through this period smoothly. “We are not the sources of problems; we are the resources that are needed to solve them. We are not expenses; we are investments. We are not just young people; we are people and citizens of this world.” (From the Children’s Statement, UN Special Session on Children, May 2002)